Pedagogia empreendedora: um estudo sobre o empresariamento de si a partir da metáfora do sonho - Mengue, Agnes Piangers (Universidade do Vale do Rio dos Sinos, 2019)
The present study analyzed the entrepreneurial pedagogy of Fernando Dolabela in order to understand what assumptions this pedagogy places in circulation and how it contributes to the proliferation of entrepreneurial education in schools, once this discussion is strengthened in the current scenario of Brazilian education. Dolabela was known by the scholars of this field as the "Monster of entrepreneurship", since he was the one who created the term and the concept of entrepreneurial pedagogy. This methodology can be applied in the initial years (4 years old) and continue until university, based on the idea of the collective dream. The author has a vast literature focused on the theme of entrepreneurial pedagogy, with a total of fifteen books. The empirical material of this research was composed by four works of the author, which were studied from a documentary analysis. They are: Oficina do empreendedor (1999), which explains the methodology of the Entrepreneurial Pedagogy created by the author; Pedagogia Empreendedora (2003), A ponte mágica (2004) e O segredo de Luísa (2008); that are part of the educational material delivered to teachers, in order to the method of entrepreneurial pedagogy be disseminated and taught in schools. The works were studied from three analytical ways: it’s necessary to criticize the school to reform it; The dream as a mobilizing factor of Entrepreneurial Pedagogy and Entrepreneurship as an imperative of our time. The articulation between the three analytical ways provided support for the understanding of the strengthening of the learning society and the emptying of the functions of the school and the place of teaching; of the proliferation of reformist discourses that depotalize the school as a space of equality and social justice and strengthen the entrepreneurial processes of the subjects; the accountability of the subjects for their successes and failures from the metaphor of the dream and the erasure of social inequalities and entrepreneurship as an imperative of our time.
Keywords: Pedagogia empreendedora; Educação empreendedora; Empresariamento de si; Sonho; Fernando Dolabela; Entrepreneurial pedagogy; Entrepreneurial education; Self-management; Dream; Fernando Dolabela; ACCNPQ::Ciências Humanas::Educação